Ensino de geografia: diversidade metodológica como princípio motivador da aula - Surmacz, Elaine Cristina Soares (2015)
The basic concern is look for evidences of motivating methodologies of the learning in the pedagogical practice of Geography teachers. We seek evidences of commitment of the teacher with the school subject learning at school routine. Our methodological orientation was based on the qualitative approach. The field work counted on different forms of data collection: interviews with teachers; observation in classroom and of the classroom; analysis of official and technical pedagogical documents that guide the daily practice of the teacher. The place of the research was two state schools of Paraná: the place of the research was two state schools of Paraná: one in the teaching modality of Field School and other in the common modality of Basic Education as research's interlocutors we count with hundred and two students of sixth grade of elementary school of the public network teaching of the Paraná state and four Geography teachers. We realize that the Geography teaching in the studied reality, it still maintains mnemonic and bookish features, being the textbook an indispensable partner; the social inequality is pointed out as an important learning factor and the proposal of an inclusive school doesn't happen in fact. We also see that the teacher is the main responsible by motivation of the student learning of geographic contents; that his methodological choices mobilize the student for learning and that the planning is essential to guarantee the success of this learning. At the end of this research, we consider that the search for dialog between the school subjects it is necessary and that there is the need of the teacher realizes himself as an intellectual transformer of the society.